Effectiveness of tax incentives to boost (retirement) saving: Theoretical motivation and empirical evidence - Orazio P. Attanasio; James Banks; Matthew Wakefield (Institute for Fiscal Studies (IFS), 2004)
The adequacy of household saving for retirement has become a policy issue all around the world. The UK and US have been in the vanguard of those countries that have tried to encourage retirement saving by providing tax-favoured treatment for particular savings accounts. We consider empirical evidence from these two countries regarding the extent to which funds in some specific tax advantaged accounts (IRAs in the US, TESSAs and ISAs in the UK) represent new savings. Our best interpretation of this evidence is that: only relatively small fractions of these funds can be considered to be new saving and so these policies have been an expensive means of encouraging saving; there has been some deadweight loss from the policies associated with reshuffling of existing savings. Continuing improvements in data on individual financial behaviour create scope for future empirical analysis of incentives to save, both within the standard economic framework that we explain and exploit, and by considering extensions to and adaptations of it.
Keywords: D91; H39; 330; Saving; tax incentives to save; lifecycle model; household behaviour; Steuerbegünstigung; Private Rentenversicherung; Konsumentenverhalten; Lebenszyklus; Vergleich; Großbritannien; USA